The ups and downs of coping and sport achievement: An episodic process analysis of within-person associations - Gaudreau, P.; Nicholls, A.; Levy, A. (Journal of Sport & Exercise Psychology, 2010)
This study examined the relationship between coping and sport achievement at the within-person level of analysis. Fifty-four golfers completed diary measures of coping, stress, and sport achievement after six consecutive rounds of golf. Results of hierarchical linear modeling revealed golfers` episodic task-oriented coping and disengagement-oriented coping were associated, respectively, with their better and worst levels of subjective and objective achievement. Distraction-oriented coping was not significantly associated with achievement. These results were obtained after accounting for between-subjects differences in ability level and for within-person variations in perceived stress across both practice and competitive golf rounds. These results contribute to an emerging literature on the relationship between coping and sport achievement, and highlight the promises of an episodic process model of sport achievement to understand the transient self-regulatory factors associated with within-person variations in athletic achievement.